2019
DOI: 10.1186/s12199-019-0824-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of scabies among schoolchildren in Dabat district, northwest Ethiopia, 2018

Abstract: BackgroundScabies is a skin infestation caused by the mite Sarcoptes scabiei that causes a pruritic skin eruption. In Ethiopia, the disease is common especially during natural or manmade disasters such as flooding, drought, civil war and conflict, poor water supply and sanitation, and overcrowding living condition. Though scabies is becoming a major public health problem, especially in low resource settings, there has been no study that reported the prevalence of scabies in the study area. The aim of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
61
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(89 citation statements)
references
References 30 publications
18
61
1
9
Order By: Relevance
“…This finding is consistent with study conducted in Gondar town, 22.5% [ 14 ]. However, our finding is higher when compared to findings from other countries such as Solomon Islands, 19.2% [ 15 ], Fiji, 18.5% [ 16 ], Germany 10.5% [ 6 ], Nigeria 13.3% [ 17 ], Cameroon 17.8% [ 18 ] and Dabat 9.3% [ 19 ]. But it is lower than from the finding of the studies conducted in India, 90.1% [ 20 ] and Pakistan, 38.15% [ 21 ], and Illu Aba Bora zone (63.5%) [ 22 ].…”
Section: Discussioncontrasting
confidence: 83%
“…This finding is consistent with study conducted in Gondar town, 22.5% [ 14 ]. However, our finding is higher when compared to findings from other countries such as Solomon Islands, 19.2% [ 15 ], Fiji, 18.5% [ 16 ], Germany 10.5% [ 6 ], Nigeria 13.3% [ 17 ], Cameroon 17.8% [ 18 ] and Dabat 9.3% [ 19 ]. But it is lower than from the finding of the studies conducted in India, 90.1% [ 20 ] and Pakistan, 38.15% [ 21 ], and Illu Aba Bora zone (63.5%) [ 22 ].…”
Section: Discussioncontrasting
confidence: 83%
“…Students who were 11 years were found to have increased risk of getting scabies than those who were 14 years of age. Similar observation was reported by Jose and Dagne et al 3,4 A student accompanied by more than 2 persons while sleeping were found to be at increased risk of getting scabies than those who were accompanied by either 2 or less than 2 persons. These findings are comparable to studies conducted by Tunje et al 14 A person living in kutcha house is at 10 times increased risk of getting scabies infection than a person living in either pucca or a semi pucca house.…”
Section: Discussionsupporting
confidence: 86%
“…10 A study done by Dange et al reported that prevalence of 9.3% among school children in northwest Ethiopia. 3 Another study conducted by Steer et al reported a similar prevalence of 18.5%.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Finally, twelve studies were included in this systematic review and meta-analysis. Of those included studies, eight studies were estimated the prevalence [8,14,[26][27][28][29][30][31] and eight studies were identified associated factor of scabies [14,27,28,[31][32][33][34][35] Fig. 1.…”
Section: Description Of Identified Studiesmentioning
confidence: 99%